Optimal configuration of Protvino to ORCA experiment for hierarchy and non-standard interactions - Dinesh Kumar Singha (Journal of High Energy Physics, 2022)
Abstract In this paper, we study the hierarchy sensitivity of Protvino to ORCA (P2O) experiment in three flavour scenario as well as its sensitivity to non-standard interactions (NSI) in neutrino propagation. Because of the largest possible baseline length of 2595 km, P2O is expected to have strong sensitivity towards neutrino mass hierarchy and NSI parameters. In our study, we show that even though the number of appearance channel events for the minimal configuration of P2O are higher compared to DUNE, still the hierarchy sensitivity of P2O is less than DUNE because of large background events. Our results show that for a background reduction factor of 0.46 and appearance channel background systematic normalization error of 4%, the hierarchy sensitivity of P2O becomes equivalent of DUNE for δ CP = 195°. We call this configuration of P2O as optimized P2O. Regarding the study of NSI, we find that, for ϵ eμ (ϵ eτ ) sensitivity of DUNE is similar (better) as compared to optimized P2O when both ϵ eμ and ϵ eτ are included in the analysis. Our results show that in presence of NSI, the change of hierarchy sensitivity with respect to standard three flavor scenario, is higher in P2O as compared to DUNE. Further, hierarchy sensitivity in presence of NSI is lower (higher) than sensitivity in the standard three flavour scenario for δ CP = 270°(90°). It is important to note that hierarchy sensitivity of optimized P2O does not get significantly better than DUNE for the current favourable values of δ CP which is 180° < δ CP < 360° as obtained by the global analysis in both standard three flavour and in presence of NSI.